Clouds and Fronts. Onto-meteorology and Philosophical Fantastic - Manchev, Boyan; Popova, Katerina (Identities: Journal for Politics, Gender and Culture, 2018)
Author(s): Boyan Manchev Title (English): Clouds and Fronts. Onto-meteorology and Philosophical Fantastic Translated by (Bulgarian to English): Katerina Popova Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 46-53 Page Count: 8 Citation (English): Boyan Manchev, “Clouds and Fronts. Onto-meteorology and Philosophical Fantastic,” translated from the Bulgarian by Katerina Popova, Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 46-53.